Importance of Participant-Centricity and Trust for a Sustainable Medical Information Commons. Issue 1 (2019) - McGuire, Amy L.; Majumder, Mary A.; Villanueva, Angela G.; Bardill, Jessica; Bollinger, Juli M.; Boerwinkle, Eric; Bubela, Tania; Deverka, Patricia A.; Evans, Barbara J.; Garrison, Nanibaa' A.; Glazer, David; Goldstein, Melissa M.; et al.
Abstract : Drawing on a landscape analysis of existing data-sharing initiatives, in-depth interviews with expert stakeholders, and public deliberations with community advisory panels across the U.S., we describe features of the evolving medical information commons (MIC). We identify participant-centricity and trustworthiness as the most important features of an MIC and discuss the implications for those seeking to create a sustainable, useful, and widely available collection of linked resources for research and other purposes.